Capacity building for land administration and 3D geo - information : issues, experiences and way forward :Powerpoint - Tuladhar, A.M. (University of Twente, 2020)
This lecture presents: General Information; Land Governance; International Initiatives; 3D Geo-information; Capacity building; Way forward.